Prolonged Febrile Seizures and Temporal Lobe Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The presence of spontaneous limbic seizures using chronic video monitoring with concurrent hippocampal and cortical EEGs, in adult rats (starting at 3 months of age) that had sustained experimental febrile seizures (FS) on postnatal day 10 was compared to hyperthermic control rats whose FS had been controlled, in a study at University of California, Irvine, CA, and University of Pennsylvania, Philadelphia.